Dopamine crosslinked graphene oxide membrane for simultaneous removal of organic pollutants and trace heavy metals from aqueous solution. Issue 23 (2nd December 2018) - Wang, Jing; Huang, Tiefan; Zhang, Lin; Yu, Qiming Jimmy; Hou, Li'an
ABSTRACT: A graphene oxide-polydopamine-(β-cyclodextrin) (GPC) ultrafiltration membrane was fabricated by using the method of drop-coating combined with vacuum filtration. The prepared GPC membrane was characterized with FTIR and XPS spectrophotometry and evaluated for its performances for the rejection of organic molecules (methylene blue) and adsorption of trace heavy metals (Pb 2+ ) from aqueous solutions. The membrane exhibited an excellent rejection coefficient of 99.2% for methylene blue and the permeation flux was 12 L m −2  h −1 at 0.1 bar. The membrane also exhibited fast adsorption kinetics for Pb 2+ and the adsorption capacity was 101.6 mg g −1 at a solution pH of 6. The performance of the membrane could almost be completely recovered after a simple clean and regeneration process. These results indicate that the GPC membrane has potential applications in treatment of complex industrial wastewater streams. GRAPHICAL ABSTRACT: